HISTORY AND EDUCATION VALUES ON SENI BELUK THAT EXIST IN CILETUH-PALABUHANRATU UNESCO GLOBAL GEOPARK - saprudin, saprudin; Somantri, Dody A (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
Ciletuh Palabuhanratu UNESCO Global Geopark (CPUGGp) is one of the Global Geopark Network (GGN) that located in Sukabumi West Java Indonesia. The Elements of Geopark that are Geo Diversity, Bio Diversity and Cultural Diversity. In this paper focusing on Cultural Diversity that many kinds of culture in CPUGGp. Culture diversity consist of Tangible and Intangible culture. Seni Beluk is one of the intangibles that the performance art which is the people as the artists (Tukang Beluk) has the good sound because they should have high sound. Seni Beluk that still exist around CPUGGp. Seni Beluk has the role on forming geology, biology and culture around CPUGGp. When beluk perform on the event, we can look at the the values especially non formal education. The values of education on Seni beluk such as- cooperation, mutual cooperation, communication and silaturahmi. These values are really important because the area of CPUGGp is very largest so Seni Beluk is one of the media for making cooperation and communication.